Intrapleural Streptokinase as Adjunctive Treatment in Empyema - Nepal, P; Maskey, D (Journal of Chitwan Medical College, 2013)
Pulmonary infections with secondary pleural involvement lead to considerable morbidity and mortality. Accepted management consists of systemic antibiotics and drainage of pleural cavity, achieved either by chest tube drainage or surgery. Open thoracotomy or video-assisted thoracoscopic surgery (VATS) achieve best drainage in gross empyema or loculated effusions but are limited by operative risk, cost and local availability. Intrapleural instillation of fibrinolytic agents like streptokinase dissolves fibrinous clots and membranes to prevent fluid sequestration and hence improve drainage. We report a case of 40 years old female with loculated empyema who was treated with adjunctive installation of serial intrapleural streptokinase after ultrasound guided pigtail insertion. Significant and early improvement of the symptoms and pathophysiology were achieved. DOI: http://dx.doi.org/10.3126/jcmc.v3i3.8636 Journal of Chitwan Medical College 2013; 3(3): 31-32